Fitting Music Composition Studies for the 21st-Century American University. - Campion, EdmundJ. (Contemporary Music Review, 2012)
I offer a brief assessment of the state of music composition in the United States today, with a focus on current conditions for American universities with advanced programs in music composition not linked with music conservatories. I trace my own experiences beginning with graduate studies at Columbia University in the 1980s, and leading to my role as Professor of Music Composition at the University of California, Berkeley and Co-Director at the Center for New Music and Audio Technologies. I end with a laundry list of things I have learned about music composition, what I value in teaching, how I teach, and what advice I have for emerging composers in the United States.